Project-Based Learning: A Learning Strategy for Acquiring 21st Century Skills - Wolff, Susan J. (Educational Facility Planner, 2007)
In today's world, learning is not confined to a classroom, school or college, and is an essential part of everyday lives and continues throughout life. New technologies have created additional avenues and enhancements for learning. Creating environments that embrace communities, celebrate cultural differences, nurture and hone practical and advanced skills, and encourage innovation and collaboration is the implicit challenge in designing 21st century education facilities.
Keywords: apprentissage par projet; coopération